Pengaruh Kesadaran Wajib Pajak, Efektivitas Sistem Perpajakan, dan Sanksi Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi di Lingkup DKI Jakarta - Rosita Meydianti; Aqamal Haq (Publikasi Indonesia, 2022)
This study aims to analyze the effect of taxpayer decisions, the effectiveness of the taxation system, and tax sanctions on individual taxpayer compliance in DKI Jakarta. The research method uses quantitative with hypothesis testing to explain the influence between variables. This study uses primary data obtained from the results of questionnaires that have been distributed to individual taxpayers in DKI Jakarta. The sample selection method used conveinence sampling method. Samples that meet the criteria are 92 people. The analysis technique in this research is multiple linear regression. Hypothesis testing using SPSS 24 analysis tool. Based on the results of the analysis shows taxpayer awareness, effectiveness of the taxation system, and tax sanctions have a positive and significant effect on individual taxpayer compliance within DKI Jakarta.